2021
DOI: 10.1021/acsomega.1c00030
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2: The Road Less Traveled—From the Respiratory Mucosa to the Brain

Abstract: Neurological manifestations have been reported in COVID-19; however, the route used by SARS-CoV-2 to enter the brain is still under debate. Recent studies have focused on the olfactory route. SARS-CoV-2 viral proteins were also detected in the glossopharyngeal and vagal nerves originating from the lower brainstem and in isolated cells of the brainstem. Our proof of concept in vivo real-time imaging study of mice using an indocyanine green dye indicated that the neurovascular component of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…However, nasal drops applied topically on the nasal mucosa of the mouse showed the distribution of the drug in the brain only at the midline. The study also showed that the drug was transported to both eyes, and slightly more fluorescence was detected in the contralateral eye …”
Section: Results and Discussionmentioning
confidence: 80%
“…However, nasal drops applied topically on the nasal mucosa of the mouse showed the distribution of the drug in the brain only at the midline. The study also showed that the drug was transported to both eyes, and slightly more fluorescence was detected in the contralateral eye …”
Section: Results and Discussionmentioning
confidence: 80%
“…The study also showed that the drug was transported to the eyes. The maxillofacial route showed slightly more fluorescence in the contralateral eye 36 .…”
Section: Discussionmentioning
confidence: 90%
“…Patients will ultimately require device-assisted therapies to manage motor fluctuations [ 13 ]. Recently, in vivo animal studies have shown that drugs can be successfully delivered into the brain through the maxillofacial route via the paravascular, vascular, perineural, lymphatic, and glymphatic pathways [ 14 , 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%